The Religious Values On Social Studies Learning Material Of The Biography Of Sheikh Salman Al-Farisi (1858 – 1928) - Muhammad Rezky Noor Handy; Didin Saripudin; Erlina Wiyanarti; Ersis Warmansyah Abbas; Mutiani Mutiani (Universitas Lambung Mangkurat, 2025)
This study focuses on Sheik Salman Al-Farisi's biography, including his early life, education period, period of teaching Islam, death and karamah he owned, and a study of religious values. The method used in this study is a literature study by reviewing various relevant sources such as Manakib, Books, scientific journal articles, and other studies related to Sheikh Salman Al Farisi, with steps of data collection, analysis, and data verification to complete writing in this article. Sheikh Salman Al-Farisi, known as Datu Gadung, was born in Dalam Pagar, Martapura, in 1858 AD and died in Gadung Village, Tapin Regency, in 1928; he was one of the religious figures in Tapin Regency; he studied religious knowledge including the Qur'an and Hadith, Tauhid, Fiqh, Tasawuf and had also studied Astronomy while in Mecca, which he taught to the people of Gadung Village and its surroundings. Sheikh Salman Al Farisi has the charisma of a prominent cleric respected by society. The religious values that can be taken are his exemplary behavior in studying and spreading Islam, his patience, and his sincerity in living his life.